Excitation Conditions for Surface-Enhanced Hyper Raman Scattering With Biocompatible Gold Nanosubstrates - Dusa, Arpad; Madzharova, Fani; Kneipp, Janina (Frontiers in Chemistry, 2021)
Surface enhanced hyper Raman scattering (SEHRS) can provide many advantages to probing of biological samples due to unique surface sensitivity and vibrational information complementary to surface-enhanced Raman scattering. To explore the conditions for an optimum electromagnetic enhancement of SEHRS by dimers of biocompatible gold nanospheres and gold nanorods, finite-difference time-domain (FDTD) simulations were carried out for a broad range of excitation wavelengths from the visible through the short-wave infrared (SWIR). The results confirm an important contribution by the enhancement of the intensity of the laser field, due to the two-photon, non-linear excitation of the effect. For excitation laser wavelengths above 1000 nm, the hyper Raman scattering (HRS) field determines the enhancement in SEHRS significantly, despite its linear contribution, due to resonances of the HRS light with plasmon modes of the gold nanodimers. The high robustness of the SEHRS enhancement across the SWIR wavelength range can compensate for variations in the optical properties of gold nanostructures in real biological environments.